Skeletal maturation associated with lower limb muscles flexibility in highly trained young soccer players - Materne, O.; Farooq, A.; Chamari, K.; Johnson, A.; Greig, M.; McNaughton, L. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Flexibility has been shown to be a key factor for performing football-specific tasks (Garcia-Pinillos et al., 2015) in youth soccer. Yet, the understanding of changes in lower limb muscle flexibility during maturation, remain limited. This study examined the relationship between skeletal age and the flexibility of the lower limb muscle groups in young elite Qatari soccer players. It was hypothesized that skeletal maturity status influences the flexibility of the lower limb muscles. Methods: 188 youth soccer players (Mean: age: 14.4±1.5 years; weight: 50.7±10.9 kg; height: 162.5±10.7 cm) were measured in pre-season screening over six consecutive years in six different age groups (U13 to U18). Flexibility of eight muscle groups (quadriceps, hamstrings, adductors, hip flexors, gastrocnemius, soleus, hip medial-, and hip lateral- rotators) were bilaterally and consistently measured using a reliable method (Fourchet et al., 2012). Skeletal age (SA) was estimated by an experienced observer using the Fels method. Linear mixed model analysis was used to compare the flexibility with maturity status (SA minus chronological age: Late (L): > - 1 year; Normal (N): +/-1 year; Early (E): < 1 year) within each age group. Results: Data from 852 limbs for each muscle group were available for analysis. Flexibility of all lower limb muscle groups decreased significantly with age. Substantial variations within identical age categories but different maturity status were reported, e.g. Quadriceps (U16: E: 128.2±0.9° > N: 132.7±1.3° > L: 141.7±4.5°, p<0.05); Gastrocnemius (U16: E: 11.4±0.7° > N: 14.7±0.9°, p<0.05); Soleus (U16: E: 28.5±0.8° > N: 33.7±1.1° > L: 39.5±3.9°, p<0.05); Medial rotator (U16: E: 49.2±1.6° > N: 54.9±1.6°, p<0.05); Hamstring (U14: E: 65.9±1.3° > N: 67.8±1.3° > L: 83.7±5.1°, p<0.05); Adductor (U15: E: 57.1±0.9° > N: 60.1±0.8° > L: 71.1±3.6°, p<0.05); Lateral rotator (U15: E: 36.4±1.2° > N: 37.7±1.2° > L: 49.7±4.9°, p<0.05). Hip flexors did not show any substantial difference between the maturity status in any age group. Conclusion: This study revealed that lower limb muscle flexibility changes through skeletal maturation and appeared to be muscle group dependent. Such information will enhance the understanding of lower limb flexibility changes during maturation, and will help youth soccer academies to initiate appropriate developmental strategies.